Case reportVaginal cuff dehiscence after intracavitary brachytherapy for endometrial cancer - Albuquerque, Kevin; Shah, Karan; Potkul, Ronald (Journal of Contemporary Brachytherapy, 2012)
We describe 2 unusual cases of vaginal dehiscence after intracavitary brachytherapy performed following robotic laparoscopic hysterectomy (RLH) along with their management. This unusual complication, which may be more common because of the robotic procedures, can be prevented by careful examination and possible delay of the onset of brachytherapy, if indicated. Our report reviews techniques of avoiding this complication and suggests that these complications should be discussed with the patients.